Die Entscheidungen des 'Dispute Settlement'-Verfahrens der WTO im Hormonstreit zwischen der EU und den USA - Implikationen fur̈ den zukun̈ftigen Umgang mit dem SPS-Abkommen - Marc Christopher Kramb (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– The decision of the WTO dispute settlement in the hormone dispute between the EC and the USA - implications for further handling of the SPS-agreement Institutions should reduce uncertainty and the costs of transaction with their regulating activities. This target was pursued at an international level with the foundation of the WTO. With an extensive treaty and a new dispute settlement procedure, the WTO was founded as the institutional platform for international co-operation. In view of the growing conflicts in international trade, the hope to create with this institution an international trade order, in which legally comprehensible decisions dominate and power-oriented politics are deterred, is fading. The case of the hormone dispute shows that the target of a fast harmonization of international standards cannot be reached in critical trade disputes. A solo effort in the area of trade measures that is introduced with the reason to protect consumers is still possible.
Keywords: 330; Internationale Handelspolitik; Fleischmarkt; EU-Staaten; USA; Hormon